1988
DOI: 10.1104/pp.88.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon Isotope Composition (δ13C), Water Use Efficiency, and Biomass Productivity of Lycopersicon esculentum, Lycopersicon pennellii, and the F1 Hybrid

Abstract: Three tomatoes, Lycopersicon esculentum Mill. cv UC82B, a droughttolerant wild related species, Lycopersicon pennellii (Cor.) D'Arcy, and their F, hybrid, were grown in containers maintained at three levels of soil moisture. Season-long water use was obtained by summing over the season daily weight losses of each container corrected for soil evaporation. Plant biomass was determined by harvesting and weighing entire dried plants. Season-long Indirect means to evaluate WUJE,, accurately in field-grown plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(117 citation statements)
references
References 29 publications
6
107
1
3
Order By: Relevance
“…We believe that indeed plants from dry climate population have adapted to tolerate drought by allocation more carbon to roots and maintaining higher WUE, since our results point in the same direction as the earlier studies (Martin and Thorstenson, 1988;Cregg, 1994;Leroux et al, 1996;Schulze et al, 1998;Osorio et al, 1998). Furthermore, our results also showed that changes in WUE were correlated with a large set of parallel changes in plant properties such as Rs and Sla.…”
Section: Discussionsupporting
confidence: 78%
“…We believe that indeed plants from dry climate population have adapted to tolerate drought by allocation more carbon to roots and maintaining higher WUE, since our results point in the same direction as the earlier studies (Martin and Thorstenson, 1988;Cregg, 1994;Leroux et al, 1996;Schulze et al, 1998;Osorio et al, 1998). Furthermore, our results also showed that changes in WUE were correlated with a large set of parallel changes in plant properties such as Rs and Sla.…”
Section: Discussionsupporting
confidence: 78%
“…We therefore examined whether gene-expression patterns might have been altered during domestication or in response to natural selection by contrasting S. lycopersicum var. M82 and the desert adapted S. pennellii (37)(38)(39)(40). Gene-expression values between S. lycopersicum and S. pennellii were compared across a panel of six tissue types, including root, vegetative, and floral tissues.…”
Section: Characterization Of Sequence Diversity In Wild and Cultivatedmentioning
confidence: 99%
“…In recent years much attention has been devoted to the study of carbon isotope composition (d 13 C) of plant tissues (Farquhar and Richards, 1984;Martin and Thorstenson, 1988;Osorio and Pereira, 1994;Leroux et al, 1996;Li et al, 2000;Amdt et al, 2001) and d 13 C has been developed as a tool to measure WUE, because a strong correlation is found between d 13 C and WUE (Farquhar et al, 1989). The carbon isotope ratio of plant tissue provides an integrated measurement of internal plant physiological and external environmental properties influencing photosynthetic gas exchange over the time when the carbon was fixed (Anderson et al, 1996;Brodribb and Hill, 1998;Ponton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%